A novel concentrated photovoltaic-driven membrane distillation hybrid system for the simultaneous production of electricity and potable water. (December 2020) - Elminshawy, Nabil A.S.; Gadalla, Mamdouh A.; Bassyouni, M.; El-Nahhas, Kamal; Elminshawy, Ahmed; Elhenawy, Y.
Abstract: Desalination powered by solar energy appears to be an attractive solution to water shortage in isolated and remote regions of low demand and a lack of a proper continuous electricity supply. This article studies the integration of cooled concentrator photovoltaic module (CPVC ) and membrane distillation (MD), proposing a novel cogeneration system designed to produce clean electricity while simultaneously devoting the excess heat extracted (HR) during cooling process to water desalination for isolated regions rich in insolation. The performance of the conceded cogeneration system is then experimentally tested outdoor under climatic conditions of Port Said, Egypt. Results indicated that the cogeneration system (CPVC -HR/MD) as a newly concept is capable to convert up to ∼83% of the solar irradiance into useful gain and can improve the CPVC module generated power by up 26.90% compared to module without cooling. Furthermore, the considered hybrid system has the capacity to produce fresh potable water of 19.58 m 3 per year with a cost of US 22.48/m 3 and to cut down the carbon dioxide release by 136.82 Kg. The results of performance and the economic analysis of the proposed system are comparable to those published for other similar solar desalination systems. Highlights: The performance of a CPV module integrated with BWHE as a cooling system was measured. A novel cogeneration CPVC -HR/MD of both electricity and fresh potable water was examined. CPVC generated power is improved by up to 26.90%. CPVC -HR/MD is capable of producing a fresh water of 19.58 m 3 per year with a cost of 22.48/m 3 . Global average of CO2 emission was reduced by about 136.82 kg/year.